Understanding external cervical resorption patterns in endodontically treated teeth. (27th February 2017) - Mavridou, A.‐M.; Hauben, E.; Wevers, M.; Schepers, E.; Bergmans, L.; Lambrechts, P.
Abstract: Aim: To understand the patterns of external cervical resorption (ECR) in endodontically treated teeth. To compare characteristics and mechanisms of ECR in root filled teeth with those established in teeth with vital pulps. Methodology: Seven cases of endodontically treated permanent teeth displaying ECR were investigated. ECR diagnosis was based on clinical findings and radiographic examination with cone‐beam computed tomography. The extracted teeth were further analysed by a nano‐focus computed tomographic (nano‐CT) system, hard‐tissue histology and scanning electron microscopy (SEM). To make a comparison with teeth with vital pulps, representative cases with ECR were also included. Results: All endodontically treated teeth had a similar ECR pattern. This pattern reflected many similarities to that seen in teeth with vital pulps; that is, three stages were observed namely initiation, resorption and repair. In particular, during the initiation stage (1st stage), the resorption started below the gingival epithelial attachment, at the level of cementum. In the resorption stage (2nd stage), ECR spreads towards the treated pulp space and in a coronal–apical direction, creating multiple resorption channels. The pulp and the pericanalar resorption resistant sheet (PRRS) had been removed during root canal treatment and thus offered no retarding or defence mechanism towards ECR. In the reparative stage (3rd stage), reparative hard‐tissue formation occurred at a localized scale. Conclusions: Similar ECR patterns were observed in all examined teeth. These patterns consisted of an initiation, a resorption and a reparative stage. Some differences were noticed between endodontically treated and teeth with vital pulps, mainly in the resorption and reparative stages. The resorption stage in root filled teeth was more intense than the repair stage, as many clastic cells and abundant granulation tissue were observed in all samples. This is possibly due to the absence of the pulp and protective PRRS layer and/or to the altered chemical composition of the root dentine after root canal treatment. Furthermore, at the repair stage, formation of reparative bonelike tissue took place to a lesser extent in root filled teeth.